Effect of the Si content on structure and mechanical properties in Al1-xSixN materials. (July 2016) - Nguyen, Trang T.; Nguyen, Thao T.; Nguyen, Giang T.; Le, Vinh V.
Abstract: Molecular dynamics simulations of Al1-x Six N samples with different Si content were carried out to investigate their structures, void distributions and mechanical properties. Such effects on other microscopic characteristics, such as bond-length distance, bond-angle and coordination number distribution have been observed. Based on the common neighbor analysis, we found that Si3 N4 sample has amorphous state and AlN sample has major amorphous phase mixed with crystalline AlN. The Al1-x Six N samples show the structures of crystalline and amorphous AlN segregated with amorphous Si3 N4 . The crystalline phase contains major fcc-AlN and minor hcp-AlN. The AlN region is compressed by amorphous Si3 N4 region and becomes more denser with increasing Si content. The mostly big voids locate in the Si3 N4 regions. The volume of voids increases but the radii of voids decrease with increasing Si content. The strengthening enhancement is observed in the Al0.5 Si0.5 N sample with denser phases and the lowest ratio nhcp-AlN /nfcc-AlN. Highlights: The structures of Al1-x Six N samples are affected by the addition of Si content. Major crystalline and minor amorphous AlN are segregated with amorphous Si3 N4 . The AlN region compressed by a-Si3 N4 becomes more denser with increasing Si content. The strengthening enhancement is observed in the Al0.5 Si0.5 N sample.